How to assure valid assessments and detect cheating in synchronous remote tests - Rodríguez Morales, Pilar (2020)
The passage from face to face teaching to distance learning, as a measure to face the COVID-19, brought about the need for the validation of the tests’ results taken in electronic format. It is considered that students are more likely to commit fraud in tests conducted remotely. The objective of the article is to present the study of the academic cheating as a report to the analysis of the psychometric validity of the tests. Through a bibliographic review, the concept of academic cheating and its types are analyzed. The main methods to detect it are presented, which can be used to ensure the validity of the results in synchronous tests, multiple choice type. The uses, potentialities and limitations of the methods used are described. Finally, the main challenges to overcome to validate the synchronous test’ results carried out remotely are presented.